Vulnerability Assessment Of Telecommunication Steel Tower Subjected To Seismic Excitation - Wong, Qi Min (Universiti Sains Malaysia, 2021)
The telecommunication towers have become a key lifeline for modern civilizations over the years since they are critical parts of communication and post-disaster networks that must continue functional after a seismic excitation. However, the towers were designed according to wind effects rather than seismic effects. As a result, the effect of the seismic on tower design and construction was not taken into account. In this study, the vulnerability assessment of the telecommunication steel tower under near-field and far-field ground motions excitations was carried out. The aim of this study is to evaluate the seismic performance of a telecommunication steel tower using vulnerability functions and to estimate the Collapse Margin Ratio (CMR) based on the near-field and far-field ground motions. The analysis procedures were carried out in a nonlinear dynamic platform. The 2D model was designed based on ASTM A 992/A 992M for steel frame members, which include beams, columns and bracings. The plastic hinges were assigned to the frame members. Nonlinear Time History Analysis (NL-THA), Incremental Dynamic Analysis (IDA), fragility analysis and CMR are performed to evaluate the seismic performance of the tower subjected to ground motions excitations by using ETABS 18 software. The IDA curves are developed and then used to generate the fragility curves. 18 sets of near-field and far-field ground motions, respectively, are used in the analyses based on the PEER and COSMOS strong ground motions database. The IDA curves are compared based on three performance levels, which is Immediate Occupancy (IO), Life Safety (LS) and Collapse Prevention (CP) by referring to the FEMA 356. The results from the IDA curves, fragility curves and the calculated CMR indicated that the seismic performance of the tower subjected to the far-field ground motion was better than the near-field ground motion. This reveals that the seismic vulnerability of the tower was greater in near-field ground motion than in the far-field ground motion. As a result, the near-field ground motion is more damaging and destructive to the tower, leading to failure or collapse of the tower.